Natural Killer (NK) cells and severity of dengue infection among children hospitalized in Dr. Sardjito Hospital - Ida Savitri Laksanawati, Umi S. Intansari (Universitas Gadjah Mada, 2008)
Background: Dengue infection isONE OF the most frequent infectious diseases in Indonesia. The manifestation of dengue infections varies from asymptomatic to live-threatening, dengue shock syndrome. It is hypothesized that immune responses contribute to immunopathogenesis of severe dengue infection. Natural killer INK) cells are innate lymphocytes which play a crucial role in anti-pathogen host defense and are particularly important in mediating resistance to viral infections. However, only a few studies of NK cells have been conducted in vivo, especially in Indonesia.ObJectives: The objectives of this study were to find the correlation between the number of NK cells with severity of the disease, and to find out the profile of NK cells absolute numbers in acute and convalescent dengue infection patients among children hospitalized n Dr. Sardjito hospitalMethods: An observational prospective study was conducted. Clinical and laboratory data were followed from the day of admission until the day of discharge. The severity of the disease was graded according to the WHO criteria for Dengue Hemorrhagic Fever IDHF). The absolute number of NK cells was measured by flow cytometer using monoclonal antibody anti-CD3, anti-CD16 + 56, and anti-CD45, with dual platform method. Student t-test was used to find out the difference of NK cell absolute number between acute and convalescent phases. The correlation between NK cells and the severity of the disease was analyzed using Spearman correlation test.Results: NK cell absolute number tended to be lower in acute compared to convalescent phase, but the difference was not statistically significant. There was an inverse correlation between the NK cell absolute number and the severity of dengue infection Ir=-O.322; p=O.017).Conclusion: Absolute number of NK cells were decreased during acute phase of dengue infection, and the decrease was more pronounced in severe than in mild dengue infection.Key words: NK cells absolute number - mild and severe dengue infection - acute and convalescent phases